Próba pomiaru zależności między rozwojem a innowacyjnością europejskiej przestrzeni regionalnej - Strahl, Danuta (An Attempt to Measure Interdependencies between the Development and Innovation of European Regional Space, 2008)
The article presents research results regarding interdependencies between regional development illustrated by the value of GDP per capita and the innovation of European regional space at NUTS-2 level, characterized by six determinants included in the Eurostat research methodology, i.e.: - share of the employed university graduates in the total number of population aged 25-64, - human resources in science and technology (HRST) as the percentage of professionally active individuals, this is an attribute representing the number of people who graduated from technical or science university faculties and who are professionally active in these fields, - share of population participating in continuing education in the total number of population aged 25-64, - employment in mid- and high-tech manufacturing industry (per cent of total labour force), - employment in high-tech services (per cent of total labour force), - EPO patents per 1 million of labour force. The above interdependencies were confirmed in two methodological attempts: by the application of statistical relations measures represented by the correlation coefficient and by means of positional classification methods. The dynamic analysis pointed to intensifying relations between the researched economic categories. The method of positional classification facilitated distinguishing four classes of European regions different in the intensity of interdependencies occurring between regional development and innovation. (original abstract)
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2008; Nr 29, s. 17-28